Efektivitas Pelayanan Publik Berbasis Aplikasi “Labanan Makmur” Pada Kampung Labanan Makmur Kecamatan Teluk Bayur Kabupaten Berau - Hesti Purnama Sari; Burhanudin; Muh. Jamal Amin (Jurnal Ilmu Pemerintahan, 2022)
This study aims to find out and describe the effectiveness of the "Labanan Makmur" application-based public service in Kampung Labanan Makmur. This study uses five focuses, namely efficiency in service, responsiveness of officers, facilities and infrastructure, spirit of cooperation, and the relationship between leaders and subordinates as well as to find out the supporting and inhibiting factors for the implementation of application-based services. The data collection techniques used were purposive sampling and accidental sampling. The results of the study show that in general the "Labanan Makmur" application-based public service in Labanan Makmur Village runs quite effectively because three of the five focuses have been running optimally. This application-based service is not efficient because only 30% of the residents of Labanan Makmur Village use this application-based service. The responsiveness of officers at the Kampung Labanan Makmur office was fast because it was in accordance with the competence of village officials. Facilities and infrastructure are adequate in supporting the running of application-based services for both the community and village officials, but the main obstacle lies in the absence of a service server belonging to the village itself. Then the spirit of cooperation seen in the Kampung Labanan Makmur office is very high and the relationship between leaders and subordinates is well established. Supporting factors in supporting the implementation of application-based public services are telecommunication networks, human resources, supporting tools/equipment and services based on village administrative platforms. Meanwhile, the inhibiting factors faced by Labanan Makmur Village were that the community was not yet familiar with online services, the mindset of the people who considered online services more difficult and the servers were down.